Does market structure matter? - Bessembinder, H.; Rath, Subhrendu (John Wiley & Sons, Inc., 2008)
We document that bid-ask spreads and volatitility decrease for stocks that moved from Nasdaq to the New York Stock Exchange (NYSE), even after the 1997 market reforms. Somewhat surprising in light of these reforms, the spread reductions are most apparent for stocks where Nasdaq liquidity providers round quotations most often. However, spreads, volatility, and trading activity are determined jointly in equilibrium, implying that simple before versus after comparisons equation framework to overcome this problem and find that decreasses in average bid-ask spreads are attributable to market structure, while reductions in volatility anad trading volume can be attributed to changes in other endogenous and exogenous variables, including the spread reduction.